Service Quality Measurement - McAlexander,Jim; Kaldenburg ,Dennis; Koenig,Hal (Journal of Health Care Marketing, 1994)
Extending the research on service quality in health care, the authors examine the efficacy of four models for measuring service quality and conclude that SERVPERF methods are superior to SERVQUAL methods. Their study found that dental patients' assessments of overall service quality were strongly influenced by assessments of provider performance. Furthermore, an examination into the causal order between perceptions of overall service quality and patient satisfaction reveals such strong reciprocal influences that it's impossible to conclude that one empirically precedes the other. Finally, the authors found that purchase intentions are influenced by both patient satisfaction and patient assessments of overall service quality.
Keywords: Marketing